The Differences of Improving Leukosit in Radiographers at Islamic Hospital Jemursari Surabaya - Farida Giyartika; Soedjajadi Keman (JURNAL KESEHATAN LINGKUNGAN, 2020)
Introduction: Health development in Indonesia is influenced by the increasing needs and demands of the community to obtain quality health services. Progress in health service facilities as a form of the use of radiation beams. The utilization of radiation substances in the field of health care is a source of danger for radiation workers in the radiology department. X-ray radiation has an impact on human health, especially the health of radiographers. The purpose of this study was to analyze the increase in leukocytes due to X-ray radiation exposure in workers exposed (radiographers) with unexposed workers (admissions officers) at the Jemursari Islamic Hospital in Surabaya. Methods: This study used an analytic observational study, using a cross sectional research design, and the analysis used was the independent t-test and mann whitney. Research subjects numbered 18 respondents taken from the population in accordance with specified criteria. Result and Discussion: The results showed there was no difference between exposed workers (radiographers) and unexposed workers (admissions officers) on increased leukocytes due to X-ray radiation exposure. Lymphocyte variables were not significantly different (independent t-test p = 0.137), monocyte variable no significant difference (independent t-test p = 0.525), neutrophil variable no significant difference (independent t-test p = 0.137), eosinophil variable no significant difference (mann whitney p = 0.27), there is no significant difference in the basophile variable (independent t-test p = 0.738). Conclusion:X-ray radiation exposure does not affect the increase in leukocytes in the blood in radiology workers.